Completely Normal Elements in Iterated Quadratic Extensions of Finite Fields of Odd Characteristics - Kyuregyan, Melsik K.; Manukyan, Ofelya A. (Mathematical Problems of Computer Science, 2021)
In this paper computationally easy explicit constructions of sequences of irreducible and normal monic polynomials over finite fields of odd characteristic are presented.